Family planning practices and prehospital care received by women seeking abortion services in a tertiary care hospital - Deb, Upasana; Tiwary, Narendra K. (International Journal Of Community Medicine And Public Health, 2021)
Background: The study was carried out in the department of Gynaecology and Obstetrics at RG Kar Medical college and Hospital, among 114 attendees seeking induced or spontaneous abortion. The aim of the study was to assess their socio demographic characteristics, elicit their family planning knowledge, practices and prehospital care received by them before coming to this institute. Methods: An observational descriptive cross-sectional study was carried out using a predesigned, pretested schedule using systemic random sampling technique among women seeking abortion services at a tertiary care centre. Results: Out of the 114 interviewees, 53 (46.5%) underwent induced abortion and rest had spontaneous abortion. Statistically significant difference was found between the mean age of induced and spontaneous abortion seekers. Majority i.e. 28 (52.8%) of induced abortion seekers first sought help at illegal abortion service providers. Statistically significant difference was found in duration of marriage, gravidity and number of living children between induced and spontaneous abortion candidates. Contraceptive knowledge and practice were found to be higher among induced abortion seekers. Conclusions: This study clearly shows the need to focus on unmet need for family planning services including safe abortion services at pre-tertiary hospital level. The Government needs to stop advertisement and sale of over the counter abortifacients which is proving to be a menace to women’s health.